Kebijakan Strategi Komunikasi Pariwisata Dinas Kebudayaan dan Pariwisata Kota Sabang Melalui Ujung Barat Festival - Muda, Indra; Barus, Rehia K.I; Bukit, Niarita (Inovasi, 2024)
The West End Festival is an annual event initiated through the collaboration of the Aceh and Sabang cultural and tourism offices. The event aims to inform and emphasize to the national and international communities that the city of Sabang is ready to welcome visitors. This research aims to understand the tourism communication strategies of the Sabang cultural and tourism office through the West End Festival event. The research is descriptive with qualitative data, and data collection techniques include in-depth interviews, observation, and literature study. The results of the research indicate that the tourism communication strategy of the Sabang cultural and tourism office through the West End Indonesia Festival is carried out using Tourism Communication Marketing (TCM), highlighting Aceh's cultural attractions accompanied by a Small and Medium Enterprises (UMKM) bazaar supported by the Sabang government and music performances by local musicians born in Sabang. The strategy further involves creating a destination brand with the title "One Island, Million Colors." Tourism communication management strategy includes promotion through social media and direct promotion using billboards and banners placed at several central points in Sabang City. Visual tourism communication strategy involves showcasing Sabang's unique crafts such as bracelets and clothing, as well as local food sold at UMKM bazaar stands. Online tourism communication strategy includes extensive pre-event promotion through social media and collaboration with influencers. In conclusion, the West End Indonesia Festival has proven to attract tourists to visit Sabang. This is evident from the high enthusiasm of the attendees during the festival and a turnover of hundreds of millions during the event.